Connecting Croatia : the public, private and civil sector of culture in the virtual space - Cvjetičanin, Biserka (Institute for International Relations, 2008)
Istraživanje o razvoju digitalne kulture u Hrvatskoj i njene uloge u međunarodnoj kulturnoj komunikaciji